A new species of marsupial frog (Hemiphractidae: Gastrotheca) from the Andes of northern Peru and first country record of Gastrotheca turnerorum - Venegas, Pablo J.; Echevarría, Lourdes Y.; García-Ayachi, Luis A.; Wong, Iván; Chávez, Germán; García-Bravo, Antonio; Catenazzi, Alessandro; Castroviejo-Fisher, Santiago (Zootaxa, 2026)
We describe Gastrotheca mittaliiti sp. nov. from the subalpine paramo of Amazonas department in the Andes of northern Peru, in the Huancabamba region, based on phylogenetic analysis of DNA sequences from three mitochondrial and two nuclear genes, genetic distances, and diagnostic morphological characters. Our phylogenetic analysis recovered the new species with high support both as part of the Gastrotheca marsupiata species group and as the sister species of G. trachyplevra. The new species can be distinguished from the rest of its congeners by the combination of the following characters: (i) moderately small size in males (SVL = 27.6–32.5 mm, n = 4); (ii) distinctly thick and elevated supratympanic fold extending from the top edge of the tympanum to the flank covered with prominent and closely packed or fused pustules; (iii) two prominent paravertebral longitudinal pustular ridges; (iv) narrow discs on fingers and toes with truncate terminal margins; (v) dorsum covered with prominent and closely packed rounded pustules; (vi) canthus rostralis thin and straight in dorsal view; and (vii) distal subarticular tubercle rounded. In addition, we report the first record of G. turnerorum in Peru and describe new morphological variation of the Peruvian populations. Our results highlight the Huancabamba region as the hotspot of Gastrotheca species richness, a result that we discuss from a biogeographic and conservation perspective.